THE ACCURACY OF THE NOTARY IN MAKING A DEED OF DISTRIBUTION AND SEPARATION OF INHERITANCE PROPERTY TO A RECOGNIZED ILL-WED CHILD - Ifa Latifa; Lina Jamilah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This research discusses the meaning and legal consequences of an illegitimate child whom his biological father recognizes with a letter of decision from the District Court but who receives an inheritance share that he should not receive following vide. 285 of the Civil Code written in the Inheritance deed and the Deed of Division and Separation of Inheritance Assets made by a Notary. The heirs only consist of 2 (two) people, namely the husband and an illegitimate child. There is no marriage agreement between husband and wife and a will. The research method used is normative juridical, using primary legal materials in the form of statutory regulations, including the Civil Code, Marriage Law No. 1 of 1974, KHI, and Customary Law. Secondary legal material was obtained from several articles that had been written by previous researchers with other problems related to illegitimate children. The results obtained are that the illegitimate child only gets ¼ share of all the assets left behind by his biological mother. The remainder is controlled by the stepfather or second husband of the illegitimate child's biological mother, who should have received 1/3 of the share if he were a legitimate child or included in the group. I.